A multi-level pore scale reactive transport model for the investigation of combined leaching and carbonation of cement paste. (January 2021) - Patel, Ravi A.; Churakov, Sergey V.; Prasianakis, Nikolaos I.
Abstract: Cementitious materials in underground constructions are exposed to CO2 rich ground waters which leads to combined carbonation and calcium leaching. Complex interplay between leaching, carbonation reaction and changes in transport pathways presents difficulty in parameterizing continuum scale models in a consistent way. Therefore, a novel multi-level pore-scale reactive transport model is presented to capture microstructure changes under combined carbonation and leaching. Model explicitly resolves capillary pores and phases with unresolved porosity as a porous media. Governing equations are solved using a lattice Boltzmann method based reactive transport solver with chemical reaction under thermodynamic equilibrium. The two-dimensional parametric study on idealized microstructures revealed that carbon content and pH of boundary solution strongly affects degradation rates, location and thickness of precipitated calcite layer. Furthermore, reactive surface area plays dominant role and tortuosity of media rather a secondary role. The three-dimensional simulations using virtual cement paste microstructure show that degradation rate exhibit non-linear behaviour with square root of time and time. This implies that simple empirical relations for prediction of progression of reaction fronts are not applicable and use of numerical reactive transport models is inevitable.. The developed model qualitatively captures the development of carbonation, leaching fronts and zonation as observed in experiments. Good quantitative agreement between modelling and experiments is obtained for initial stages. At later times, the modelling result and experimental observations diverge significantly. This discrepancy is likely due to lack of consideration of kinetics of C-S-H dissolution and calcite precipitation. Highlights: A lattice Boltzmann method based multi-level pore-scale reactive transport model for combined carbonation and leaching. Model accounts for capillary and gel pores evolution and detailed chemistry evolution through coupled thermodynamic solver. 2D simulations reveal a complex interplay between microstructure evolution and boundary solution composition. 3D simulation captures changes in cement paste microstructure due to combined carbonation and leaching.